1999
DOI: 10.1191/096032799678840219
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the carcinogenic potential of the herbicide alachlor4 to man

Abstract: Chronic bioassays have revealed that alachlor caused nasal, thyroid, and stomach tumours in rats but was not carcinogenic in mice. Significant increases in thyroid and stomach tumours were observed only at doses that exceeded the maximum tolerated dose (MTD). While nasal tumours were found at doses below the MTD, they were small and benign in nature. This publication describes the work undertaken by Monsanto to understand the carcinogenic mode of action of alachlor in the rat and to investigate the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 63 publications
2
39
1
Order By: Relevance
“…Given that mouse nasal tissue is less proficient than rat in forming critical metabolites and human nasal tissue is even less proficient than mouse (Heydens et al, 1999), the fact that the mouse is insensitive to chloracetanilide NM carcinogenicity suggests that humans would be unlikely to be responsive. In humans, no association with nasal toxicity or nasal or other tumors (Heydens et al, 1999) has been reported for chloracetanilide compounds.…”
Section: Human Effects Of Rodent Nasal Cytotoxinsmentioning
confidence: 99%
“…Given that mouse nasal tissue is less proficient than rat in forming critical metabolites and human nasal tissue is even less proficient than mouse (Heydens et al, 1999), the fact that the mouse is insensitive to chloracetanilide NM carcinogenicity suggests that humans would be unlikely to be responsive. In humans, no association with nasal toxicity or nasal or other tumors (Heydens et al, 1999) has been reported for chloracetanilide compounds.…”
Section: Human Effects Of Rodent Nasal Cytotoxinsmentioning
confidence: 99%
“…2, 2014 CONSENSUS DIAGNOSES AND MODE OF ACTION FOR THE FORMATION OF GASTRIC TUMORS 391 (i.e., parietal, chief, or ECL cells) were not recognizable Thake, Iatropoulos, et al 1995). Parietal cell number measurements in the alachlor gastric tumor promotion study demonstrated that after 1 year of treatment with 126 mg/kg/day, the numbers of parietal cells were profoundly reduced to 7% of the control value (Branch and Thake 1995;Heydens et al 1999;Tatematsu and Thake 1996).…”
Section: Loss Of Parietal Cellsmentioning
confidence: 99%
“…Since there was substantial morphologic variability within and among the gastric tumors as diagnosed in the original carcinogenicity studies (Daly 1981(Daly , 1983, reevaluations of the gastric tumors from the original bioassays for both alachlor and butachlor were previously conducted in an attempt to identify the tumor type involved and to determine whether the morphologic characteristics of tumors from the two original studies with alachlor and butachlor were comparable (Hard and Iatropoulos 1994;Hard et al 1995;Heydens et al 1999; International Agency for Research on Cancer [IARC] 2003). Also, a series of histochemical and immunohistochemical stains were used to identify features that would aid in identification of the cell/cells of origin.…”
Section: Introductionmentioning
confidence: 99%
“…Although the carcinogenic potential of alachlor and its hazardous effect are reported in a number of previous studies (EPA 1984, 1987, Heydens et al. 1999, Dearfield et al 1999and Genter et al 2002 it is still widely used in agriculture (Lee et al 2004).…”
Section: ϫ5mentioning
confidence: 99%
“…It represents a high health hazard on a toxicological basis being a carcinogen, class B2 (USEPA, 1993). Alachlor caused nasal, thyroid and stomach tumors in rats and was not carcinogenic in mice (Heydens et al 1999). Also, the herbicide induced olfactory mucosal tumors in rats in a highly ordered temporal process (Wetmore et al 1999).…”
Section: ϫ5mentioning
confidence: 99%